Astrocytes profiling in acute hepatic encephalopathy: Possible enrolling of glial fibrillary acidic protein, tumor necrosis factor-alpha, inwardly rectifying potassium channel (Kir 4.1) and aquaporin-4 in rat cerebral cortex - Elsherbini, Dalia Mahmoud Abdelmonem; Ghoneim, Fatma M.; El-Mancy, Eman Mohammed; Ebrahim, Hasnaa Ali; El-Sherbiny, Mohamed; El-Shafey, Mohamed; Al-Serwi, Rasha Hamed; Elsherbiny, Nehal M. (Frontiers in Cellular Neuroscience, 2022)
ABSTRACT Hepatic encephalopathy (HE) is neurological disarray manifested as a sequel to chronic and acute liver failure (ALF). A potentially fatal consequence of ALF is brain edema with concomitant astrocyte enlargement. The present study aims to outline the role of astrocytes in acute HE and to shed light on the most critical mechanisms driving this role. Rats were allocated into two groups. Group 1, the control group, received vehicle. Group 2, the TAA group, received TAA (300 mg/kg) for three days. Serum AST, ALT, and ammonia were determined. Liver and cerebral cortical sections were processed for hematoxylin and eosin staining. Additionally, mRNA expression and immunohistochemical staining of cortical GFAP, TNFα, Kir4.1, and AQP4 was performed. Cortical sections from the TAA group demonstrated neuropil vacuolation and astrocytes enlargement with focal gliosis. GFAP, TNFα, and AQP4 revealed increased mRNA expression, positive immunoreactivity and a positive correlation to brain water content. In contrast, Kir 4.1 showed decreased mRNA expression and immunoreactivity and a negative correlation to brain water content. In conclusion, our finding revealed altered levels of TNFα, Kir 4.1, GFAP and AQP4 in HE associated brain edema. A more significant dysregulation of Kir 4.1 and TNFα was observed compared to AQP4 and GFAP.